Are endogenous opioid mechanisms involved in the effects of aerobic exercise training on chronic low back pain?: a randomized controlled trial - Bruehl, Stephen (Pain, 2020)
Aerobic exercise is believed to be an effective chronic low back pain (CLBP) intervention, although its mechanisms remain largely untested. This study evaluated whether endogenous opioid (EO) mechanisms contributed to the analgesic effects of an aerobic exercise intervention for CLBP. Individuals with CLBP were randomized to a 6-week, 18-session aerobic exercise intervention (n = 38) or usual activity control (n = 44). Before and after the intervention, participants underwent separate laboratory sessions to assess responses to evoked heat pain after receiving saline placebo or i.v. naloxone (opioid antagonist) in double-blinded, crossover fashion. Chronic pain intensity and interference were assessed before and after the intervention. EO analgesia was indexed by naloxone-placebo condition differences in evoked pain responses (blockade effects). Relative to controls, exercise participants reported significantly greater pre-post intervention decreases in chronic pain intensity and interference (p’s < .04) and larger reductions in placebo condition evoked pain responsiveness (McGill Pain Questionnaire-Short Form [MPQ]-Total). At the group level, EO analgesia (MPQ-Total blockade effects) increased significantly pre-post intervention only among female exercisers (p = .03). Dose-response effects were suggested by a significant positive association in the exercise group between exercise intensity (based on meeting heart rate targets) and EO increases (MPQ-Present Pain Intensity; p = .04). Enhanced EO analgesia (MPQ-Total) was associated with significantly greater improvement in average chronic pain intensity (p = .009). Aerobic exercise training in the absence of other interventions appears effective for CLBP management. Aerobic exercise-related enhancements in endogenous pain inhibition, in part EO-related, likely contribute to these benefits